P15: EVALUATING THE INTERNATIONAL USABILITY OF A LOW-COST LAPAROSCOPIC TRAINER IN LOW- AND HIGH-INCOME SETTINGS. (27th April 2021) - Franco, C; Sawhney, R; Burke, J; Aruparayil, N; Chauhan, M; Bolton, W; Mishra, A; Valdastri, P; Jayne, D
Abstract: Introduction: Limited access to equipment and trained personnel restrict the adoption of laparoscopic surgery globally. There are a wide range of laparoscopic trainers available; however, most of these are not affordable. We propose an ultra-low-cost laparoscopic trainer (Lap-Pack), designed for portability, ease of assembly and compatibility with smart devices. The study aims to evaluate the usability of Lap-Pack as a training tool in low- and high-income settings. Method: An international usability study was conducted in India and the UK in 2019. The participants (n=60), consisting of senior surgeons (n=18), junior trainees (n=20) and medical students (n=22), were asked to complete two tasks using Lap-Pack. Participants then scored Lap-Pack in a 25-point questionnaire, including a pre-established Face-Validity Criteria and four major evaluation categories – Usability, Camera, View, Material. Result: Lap-Pack scored highly in Face-Validity with a combined mean score of 4.63 (95%CI: 4.31, 4.95, p <0.05) of a possible 6. In both cohorts, the Usability and Camera categories scored highest, with combined values respectively of 6.10 (95%CI: 6.01, 6.19, p <0.05) and 6.09 (95%CI: 5.88, 6.31, p <0.05) of a possible 7. For both centres, the highest-scoring individual criteria were its light weight and portability. Conclusion: Overall, Lap-Pack was received positively by medical students and consultants alike, suggesting it is a suitable device for development of skills as part of a larger laparoscopic training curriculum. Its ease of assembly, portability and versatility show promise of increasing access to training opportunities worldwide. Take-home message: Lap-Pack is an ultra-low-cost, portable laparoscopic simulator featuring compatibility with smart devices designed to help increase access to laparoscopic training worldwide. An international usability study found medical students, junior trainees and senior surgeons rated its usability and camera features highly, suggesting its employability as a laparoscopic training tool on a global scale.